METHANE AND HYDROGEN SULFIDE SEEPAGE IN THE NORTHWEST PELOPONNESUS PETROLIFEROUS BASIN (GREECE): ORIGIN AND GEOHAZARD - Etiope G.; Favali P.; Papatheodorou G.; Christodoulou D.P.; Ferentinos G.; Sokos E. (My University, 2006)
Gas seepages along the Ionian coast of the northwestern Peloponnesus (Greece), at Killini, Katakolo, and Kaiafas reflect deep hydrocarbon-generation processes and represent a real hazard for humans and buildings. Methane microseepage, gas concentration in offshore and onshore vents, and gas dissolved in water springs, including the isotopic analysis of methane, have shown that the seeps are caused by thermogenic methane that had accumulated in Mesozoic limestone and had migrated upward through faults, or zones of weakness, induced by salt diapirism. A link between local seismicity and salt tectonics is suggested by the analyses of hypocenter distribution. Methane acts as a carrier gas for hydrogen sulfide produced by thermal sulfate reduction and/or thermal decomposition of sulfur compounds in kerogen or oil. Methane seeps in potentially explosive amounts, and hydrogen sulfide is over the levels necessary to induce toxicological diseases and lethal effects. Copyright © 2006. The American Association of Petroleum Geologists. All rights reserved.